Mid-Pliocene not analogous to high-CO2 climate when considering Northern Hemisphere winter variability - A. M. Oldeman; M. L. J. Baatsen; A. S. von der Heydt; A. S. von der Heydt; A. J. van Delden; H. A. Dijkstra; H. A. Dijkstra (Weather and Climate Dynamics, 2024)
In this study, we address the question of whether the mid-Pliocene climate can act as an analogue for a future warm climate with elevated CO2 concentrations, specifically regarding Northern Hemisphere winter variability. We use a set of sensitivity simulations with the global coupled climate model CESM1.0.5 (CCSM4-Utr), which is part of the PlioMIP2 model ensemble, to separate the response to a CO2 doubling and to mid-Pliocene boundary conditions other than CO2. In the CO2 doubling simulation, the Aleutian low deepens, and the Pacific–North American pattern (PNA) strengthens. In response to the mid-Pliocene boundary conditions, sea-level pressure variance decreases over the North Pacific, the PNA becomes weaker and the North Pacific Oscillation (NPO) becomes the dominant mode of variability. The mid-Pliocene simulation shows a weak North Pacific jet stream that is less variable in intensity but has a high level of variation in jet latitude, consistent with a dominant NPO and indicating that North Pacific atmospheric dynamics become more North Atlantic-like. We demonstrate that the weakening of the Aleutian low, and subsequent relative dominance of the NPO over the PNA, is related to shifts in tropical Pacific convection. Variability in the North Atlantic shows little variation between all simulations. The opposite response in North Pacific winter variability to elevated CO2 or mid-Pliocene boundary conditions demonstrates that the mid-Pliocene climate cannot serve as a future analogue in this regard.